Reproduction of the sea urchin Tripneustes depressus (Camarodonta: Toxopneustidae) in Bahía de La Paz, Baja California Sur, Mexico - Vives, Ailet (2021)
Introduction: Sea urchin gonads (roe or uni) are considered a culinary delicacy worldwide. However, only a few species are considered edible and commercialized. The sea urchin Tripneustes depressus has generated the interest of producers in Baja California Sur, Mexico, due to the quality of its gonads. A biological basis for designing a management strategy is key to consider its commercial exploitation. Objective: To determine the reproductive season of T. depressus through description of the gonad stages and reproductive cycle, and to establish its relationship with environmental factors. Methods: We collected monthly samples (October 2016-September 2017), recording in-situ temperature and photoperiod. We evaluated a sample of 1 055 specimens for demographic characteristics, using total weight (g) and test diameter (cm). We also did a histological analysis of gonads from 178 individuals. Results: Average test diameter was 9.70 ± 0.03 cm (5-12.50 cm). Based on the proportion into the gonad of sexual (gametes) and somatic (nutritive phagocytes) cells, we propose five gonad stages (growing, premature, mature, spawning, and intergametic) for both sexes. There were two times of the year when gonads were heaviest and closely corresponded to the growing stage, coinciding with the highest proportions of nutritive phagocytes. Gonad development (growing and premature stages) peaks in the months with the longest daylight periods, with spawning in the shortest daylight periods. Conclusions: Gonad wet weight and adjusted gonad weight are good indicators of the reproductive season of T. depressus. The lowest gonad wet weights were matched the spawning peak in the shortest daylight period (January and March).